MRI of fetal spinal malformations - Huisman, Thierry A.G.M.; Graham, Ernest M.; Tekes, Aylin; Poretti, Andrea (Journal of Pediatric Neuroradiology, 2012)
Fetal magnetic resonance imaging is well accepted as secondary image tool for the evaluation of pathologies affecting the fetal brain as detected on prenatal ultrasonography. Significantly, fewer articles have focused on the fetal spinal canal and its contents. Many malformations and pathologies involving the spinal canal and cord may however have a significant impact on the quality of life. In addition, anomalies of the spinal cord may affect the development of the fetal brain or may be part of a more extensive malformation that may also affect the major thoracic and abdominal organs. A thorough knowledge of the normal and abnormal development of the spinal column and its contents is necessary to diagnose and understand the encountered findings. In the current review the value of fetal magnetic resonance imaging of the spinal column and cord is discussed. The most frequently encountered malformations will be presented and discussed in the context of the most relevant embryological processes.
Keywords: Fetal MRI; spine; malformation; myelomeningoceles; diastematomyelia; dorsal dermal sinus; sacrococcygeal teratoma